Post a New Question


posted by .

The thirteenth term of an arithmetic progrssion os 27 and the seventh term is three timees the second term. tind the first term,common difference and the sum of the first ten terms

  • maths -

    term(13) = a+12d
    so a+12d = 27 (equation #1)

    term(7) = 3term(2)
    a+6d = 3(a+d)
    a+6d = 3a + 3d
    2a - 3d = 0 (equation #2)

    It is easy to solve these two equations, (see if you can get a=3, d=-2)

    then use your formula for the sum of 10 terms.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question